Correction: Brochet et al. A Quantitative Comparison between Shannon and Tsallis–Havrda–Charvat Entropies Applied to Cancer Outcome Prediction. Entropy 2022, 24, 436 - Thibaud Brochet; Jérôme Lapuyade-Lahorgue; Alexandre Huat; Sébastien Thureau; David Pasquier; Isabelle Gardin; Romain Modzelewski; David Gibon; Juliette Thariat; Vincent Grégoire; Pierre Vera; Su Ruan (Entropy, 2022)
Alexandre Huat, Sébastien Thureau, David Pasquier, Isabelle Gardin, Romain Modzelewski, David Gibon, Juliette Thariat and Vincent Grégoire were not included as authors in the original publication [...]